LEADER IN ME WIDELY INDIVIDUAL GOAL (WIG) PROGRAM IN FORMING STUDENT LEADERSHIP CHARACTER - Afifah, Rizqi; Rugaiyah, Rugaiyah; Rahmawati, Desi (International Education Trend Issues, 2023)
Character education is very important to instill good character in someone. The character that is suitable for solving problems in the era of disruption 4.0 is a lead character that can be applied to students through the education level. The Leader in Me (LIM) program is one of the programs that function to shape the character of students to become leaders by instilling disciplinary values so that students can excel and compete in the 21st century with one of its programs, namely the Widely Individual Goal (WIG). The purpose of this study is to want to know in depth about the Leader in me program on the Widely Individual Goal (WIG) in shaping student leadership character. This research was conducted at SD Yasporbi I using a qualitative research approach using the case study method. The time of this research started from November 2022 to May 2023 with data collection techniques namely participatory observation, interviews, and documentation obtained from several informants, namely the principal, deputy principal, LIM president, students, teachers, and parents of students. The results of this research are in forming the character of student leadership, SD Yasporbi I through the Leader in me program. Developing several goals which are divided into three, including School WIG, Teachers, and Students. The three WIGs are integrated with each other so that they become an effective way to shape student leadership character.